Dumping sites in the Ljubljansko polje water protection area, the primary source of Ljubljana's drinking water - Breg Valjavec, Mateja (Acta geographica Slovenica, 2007)
Ljubljansko polje is a gravel plain lying along the Sava River north of Ljubljana. Although built-up areas are steadily expanding, the water protection area has helped preserve the character of relatively intensely cultivated agricultural land at least in its central part. However, illegal dumping sites pose a threat to the groundwater in the gravel aquifer. In the narrowest and narrow water protection areas of Ljubljansko polje, we have found, registered, and studied 1,445 illegal dumping sites with a total surface area amounting to 120,816m2 and a total volume of 209,422m3. A good seventh (13.5%) of the total waste is hazardous. In the area surveyed, we also registered 86 gravel pits, 47 information and warning signs, and 57 road barriers on access roads. In time, it will be necessary to rehabilitate all the illegal dumping sites; however, due to the large quantity of waste it is unrealistic to expect this to happen in one go, and we have therefore established a priority schedule for the rehabilitation.
Keywords: odpadki; odlagališča; podtalnica; vodni viri; vodovarstvena območja; onesnaževanje voda; Ljubljana; Ljubljansko polje